ZT‐01: A novel somatostatin receptor 2 antagonist for restoring the glucagon response to hypoglycaemia in type 1 diabetes. Issue 5 (15th February 2022) - Farhat, Rawad; Aiken, Julian; D'Souza, Ninoschka C.; Appadurai, Daniel; Hull, Grayson; Simonson, Eric; Liggins, Richard T.; Riddell, Michael C.; Chan, Owen
Abstract: Aim: To evaluate the pharmacokinetics and efficacy of a novel somatostatin receptor 2 antagonist, ZT‐01, to stimulate glucagon release in rats with type 1 diabetes (T1D). Methods: The pharmacokinetics of ZT‐01 and PRL‐2903 were assessed following intraperitoneal or subcutaneous dosing at 10 mg/kg. We compared the efficacy of ZT‐01 with PRL‐2903 to prevent hypoglycaemia during an insulin bolus challenge and under hypoglycaemic clamp conditions. Results: Within 1 hour after intraperitoneal administration, ZT‐01 achieved more than 10‐fold higher plasma Cmax compared with PRL‐2903. Twenty‐four hour exposure was 4.7× and 11.3× higher with ZT‐01 by the intraperitoneal and subcutaneous routes, respectively. The median time to reach hypoglycaemia of more than 3.0 mmol/L was 60, 70, and 125 minutes following vehicle, PRL‐2903, or ZT‐01 administration, respectively. Furthermore, rats receiving ZT‐01 had significantly higher glucose nadirs following insulin administration compared with PRL‐2903– and vehicle–treated rats. During the hypoglycaemic clamp, ZT‐01 increased peak glucagon responses by ~4‐fold over PRL‐2903. Conclusions: We conclude that ZT‐01 may be effective in restoring glucagon responses and preventing the onset of hypoglycaemia in patients with T1D.